SYNTHESIS OF SOME NOVEL TETRAZOLE SUBSTITUTED BENZIMIDAZOLES AND THEIR EVALUATION AS ANTIOXIDANTS - M.A.KALE; M.R.PEHARKAR (International Journal of Pharma and Bio Sciences, 2013)
A series of tetrazole derivatives (3a-h) were synthesized and screened for antioxidant activity by nitric oxide free radical scavenging activity. All the synthesized compounds were structurally elucidated by spectral techniques such as IR, 1H NMR spectroscopy and mass spectrometry. The compounds 3b, 3d 3f and 3h exhibited promising antioxidant activities which were found to be comparable with standard ascorbic acid.